(untitled) (The International Journal for Scientific Research, 2026)
This study aimed to investigate the impact of business development strategies, encompassing four dimensions namely innovation, market expansion, strategic partnerships and alliances, and human capital development, on organizational growth in private sector companies in the Kingdom of Saudi Arabia. The study adopted a descriptive analytical approach, and a questionnaire was distributed to a stratified random sample of 180 managers and employees at various administrative levels in Saudi private sector companies. Data were analyzed using the Statistical Package for Social Sciences (SPSS). The findings revealed a statistically significant impact at α≤0.05 of business development strategies collectively on organizational growth, indicating that the four dimensions explain 65.9% of the variance in organizational growth. The results demonstrated that innovation has the strongest impact on organizational growth, followed by human capital development, market expansion, and finally strategic partnerships and alliances. Based on these findings, the study recommended establishing specialized units for innovation and business development, developing comprehensive talent management strategies for attracting and retaining competencies, adopting a systematic approach to exploring new market expansion opportunities, fostering a culture of strategic partnerships, investing intensively in training and development programs, and accelerating digital transformation.